2015
DOI: 10.1037/pspa0000026
|View full text |Cite
|
Sign up to set email alerts
|

Cheating at the end to avoid regret.

Abstract: How do people behave when they face a finite series of opportunities to cheat with little or no risk of detection? In 4 experiments and a small meta-analysis, we analyzed over 25,000 cheating opportunities faced by over 2,500 people. The results suggested that the odds of cheating are almost 3 times higher at the end of a series than earlier. Participants could cheat in 1 of 2 ways: They could lie about the outcome of a private coin flip to get a payoff that they would otherwise not receive (Studies 1-3) or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…For example, in our design no feedback, such as external punishment for dishonesty or praise for honesty, was provided or expected. In the real world, however, other factors will likely facilitate dishonesty escalation or halt it, including feedback, opportunity and altering rewards and punishment 42,35,43.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our design no feedback, such as external punishment for dishonesty or praise for honesty, was provided or expected. In the real world, however, other factors will likely facilitate dishonesty escalation or halt it, including feedback, opportunity and altering rewards and punishment 42,35,43.…”
Section: Discussionmentioning
confidence: 99%
“…The present study attempts to contribute to existing motivational accounts of risk taking by examining how motivation shifts as individuals are approaching an ending may lead to increased risky decision making. Recent studies have suggested that individuals’ reactions tend to change toward the end of a series of tasks (Effron, Bryan, & Murnighan, 2015; Li & Epley, 2009; McKenzie et al, 2016; O’Brien & Ellsworth, 2012). In the domain of risky decision making, it has been suggested that individuals show increased risk taking at the end of a series of gambles (e.g., McKenzie et al, 2016); however, the underlying mechanism of this phenomenon remains unknown.…”
mentioning
confidence: 99%
“…For instance, participants may have viewed the 10th round and 20th round as the end of each stage, leading to shifts in risk-taking behavior. To address this concern, future studies examining the ending effect should avoid using multiples of 10 or 5 as the number of rounds or use a different number of rounds as the control group (Effron et al, 2015 ). Another possible explanation is that as the decision task continues, after several trials, people tend to become more conservative because generally, people are risk aversive (Larrick, 1993 ; Benartzi and Thaler, 1995 ).…”
Section: Discussionmentioning
confidence: 99%